2015
DOI: 10.1159/000371449
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K Antagonists Predispose to Calciphylaxis in Patients with End-Stage Renal Disease

Abstract: Background/Aims: Calciphylaxis is associated with a poor prognosis in dialysis patients, and its pathogenesis remains incompletely understood. Although the use of vitamin K antagonists (VKA) has been implicated, previous reports are conflicting. We aimed to determine if vitamin K antagonists conferred an increased risk of calciphylaxis in patients on dialysis. Methods: We performed a single-centre, retrospective cohort study of 2,234 patients receiving dialysis, and compared the characteristics of those with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 19 publications
(35 reference statements)
0
34
0
4
Order By: Relevance
“…Obesity, systemic corticosteroid as well as vitamin K antagonists use besides severe renal HPT were identified as BCT bilateral cervical thymectomy, RCT randomized controlled trial, RS retrospective study, CRS comparative retrospective study, nd no data predisposing factors in the development of calciphylaxis [66,67]. The treatment encompasses local wound care with judicious local debridement and/or excision when severe soft tissue infection ensues.…”
Section: Surgical Treatment Of Patients With Renal Hyperparathyroidismentioning
confidence: 99%
See 2 more Smart Citations
“…Obesity, systemic corticosteroid as well as vitamin K antagonists use besides severe renal HPT were identified as BCT bilateral cervical thymectomy, RCT randomized controlled trial, RS retrospective study, CRS comparative retrospective study, nd no data predisposing factors in the development of calciphylaxis [66,67]. The treatment encompasses local wound care with judicious local debridement and/or excision when severe soft tissue infection ensues.…”
Section: Surgical Treatment Of Patients With Renal Hyperparathyroidismentioning
confidence: 99%
“…Although there were no therapeutic clinical trials conducted, PTX was contemplated only in patients with PTH levels >20 pmol/l sustaining a calcium-phosphorus product consistently above 70 refractory to medical treatment (EL 2c) [70]. The estimated disease-specific survival rate for calciphylaxis 1 year after the diagnosis is 45.8 %, and patients infrequently survive longer than 2 years [66,67,70].…”
Section: Surgical Treatment Of Patients With Renal Hyperparathyroidismentioning
confidence: 99%
See 1 more Smart Citation
“…20 Furthermore, prevalence of well-described calciphylaxis risk factors such as warfarin therapy and obesity was higher in PD patients who developed calciphylaxis compared to previously published prevalence of these risk factors in HD patients who developed calciphylaxis. 3,[5][6][7]18 Thus, it is possible that it is these risk factors and not dialysis modality that dictates calciphylaxis risk. Previous studies have shown that PD is associated with more abnormalities in phosphorous and albumin than HD, especially once residual renal function has deteriorated.…”
Section: Calciphylaxis In Peritoneal Dialysismentioning
confidence: 99%
“…3,4 Diabetes mellitus, obesity, abnormalities in mineral bone parameters, and warfarin therapy have been described as calciphylaxis risk factors for HD patients. 3,[5][6][7] Cinacalcet has been reported to reduce the risk…”
Section: Introductionmentioning
confidence: 99%